EVALUASI SISTEM ZONASI TERHADAP DAYA SERAP PESERTA DIDIK (Jurnal Tata Kelola Pendidikan, 2020)
This study entitled the evaluation of the zoning system on the absorption capacity of SMANegeri 1 Cibadak. The general objective of this study is to determine the extent of thesuccess of the zoning system implemented by the government in absorbing students in SMANegeri 1 Cibadak. This study uses a descriptive method using a qualitative approach. Datacollection using the interview method. The population in this study were the principal, thehead of PPDB, and 2 teachers at SMA Negeri 1 Cibadak. The data were analyzed by datareduction and drawing conclusions in narrative form. The results showed that theevaluation of the zoning system began with the acceptance of new students using theprovisions set by Education and Culture, 50% of students from the zoning system, 25% ofthe achievement pathway, 15% of the affirmation pathway, and 5% of the parent transferpath. The quality of the school is very decisive for the results of this program, the qualityof the teachers also determines the final outcome of the students who attend SMA Negeri 1Cibadak. This is the spirit of the achievement of students and schools. For this reason, SMANegeri 1 Cibadak feels that it can accept all students in the implementation of new studentsfor the 2020-2021 school year quota of 36 people times 12 classes.
Keywords: Zoning System; Student Absorption